Pooled Analysis on the Effectiveness and Safety of Lipegfilgrastim in Patients With Urological Malignancies in the Real-World Setting - Merseburger, Axel S.; Geiges, Götz; Klier, Jörg; Wiesholzer, Martin; Pichler, Petra (Frontiers in Oncology, 2021)
Lipegfilgrastim is a long-acting glycopegylated granulocyte-colony stimulating factor (G-CSF) approved for the management of chemotherapy-induced neutropenia. In general, there is little information on the use of any G-CSFs specifically in patients with urological malignancies receiving chemotherapy. This report combines information from two prospective non-interventional studies on the prophylactic use of lipegfilgrastim in urological cancer patients receiving chemotherapy in the real-world setting. Data were derived from two phase IV studies (NADIR and LEOS) with similar protocols conducted in nine European countries. Analysis included 228 patients (142 prostate, 50 testicular, 27 bladder, and 9 other urological cancers). Chemotherapy-induced febrile neutropenia risk was classified as high (43.0%), intermediate (49.1%), or low (7.5%). Lipegfilgrastim was administered as primary (n = 180, 78.9%) or secondary (n = 29, 12.7%) prophylaxis. The incidence of febrile neutropenia over all chemotherapy cycles (n = 998) and first cycles (n = 228) for which lipegfilgrastim was administered for prophylaxis was 2.6% and 1.3%, respectively. Corresponding results for grade 3/4 neutropenia were 2.2% and 0.9%, respectively. Adverse drug reactions occurred in 24 patients (10.5%): those in more than one patient were bone pain (n = 6, 2.6%) and pyrexia (n = 3, 1.3%). The use of lipegfilgrastim for the prophylaxis of chemotherapy-induced neutropenia was effective and well tolerated in patients with urological malignancies in the real-world setting.